The Marine Isotope Stage 3 landscape around Manot Cave (Israel) and the food habits of anatomically modern humans: New insights from the anthracological record and stable carbon isotope analysis of wild almond (Amygdalus sp.). Issue 160 (November 2021) - Caracuta, Valentina; Alex, Bridget; Regev, Lior; Regev, Johanna; Mintz, Eugenia; Barzilai, Omry; Hershkovitz, Israel; Boaretto, Elisabetta
Abstract: The excavation of Manot Cave (Israel) reveals intensive occupation during the Early Upper Paleolithic and provides the first continuous set of anthracological data available for the Ahmarian, Levantine Aurignacian and post-Levantine Aurignacian periods. The paper aims to study the vegetal landscape around Manot Cave in the context of climate changes that characterized the last part of the Marine Isotope Stage 3 (MIS 3) and to address the issue of firewood and food procurement among Paleolithic hunter-gatherers. Charcoal samples recovered from the archaeological layers at Manot Cave shed light on the fuel and food procurement strategies while radiocarbon dating and stable carbon isotope analysis (Δ 13 C) of selected charcoals provide information about the ancient climate. The results show that five woody taxa were exploited at the site; Amygdalus sp. was the most common species, whereas Quercus ithaburensis, Tamarix sp., Pomoideae indet., and Pistacia atlantica were relatively rare. The representations of the recovered wooden species suggest that an open forest of almonds and oaks existed in the area during MIS 3. Radiocarbon dating of Amygdalus sp. charcoals, coupled with stable carbon isotope analysis (Δ 13 C) of modern and archaeological Amygdalus sp. clearly indicate variations in rainfall that could have decreased the density of tree cover. These analyses provide high-resolution data on the climate changes affecting the surroundings of Manot Cave between ∼46 and 28 ka cal BP and indicate two drier phases corresponding to the Ahmarian and post-Levantine Aurignacian cultures while a more humid period identified during the Levantine Aurignacian.